THE EFFECT OF GIVING KATUK LEAF VEGETABLES TO BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS IN RAJA TENGAH VILLAGE, KUALA DISTRICT, LANGKAT REGENCY IN 2021 - Saddiyah Rangkuti (Science Midwifery, 2022)
Breastfeeding is a very valuable gift that can be given by a mother to her baby, ASII provides the best nutrition for the baby as well as protection against disease. Exclusive breastfeeding can help babies for future growth and development. Physically she gets adequate nutritional intake, far more than everything the world has to offer. The purpose of this study was to determine the Effect of Giving Katuk Leaf Vegetables on Breast Milk Production in Breastfeeding Mothers in Raja Tengah Village, Kuala District, Langkat Regency in 2021. This study used a pre-experimental type of research, with a One Group pre-test and post-test design. The population in this study were all breastfeeding mothers with babies aged 0-6 months in Raja Tengah Village, Kuala District, Langkat Regency, The data collected in May-August were 20 people, the sample in this study was the Purposive Sampling Technique, with the research technique using the Chi Square test. The results of this study indicate that there is a significant effect on the milk production of pregnant women who did not increase before being given katuk leaf vegetables in Raja Tengah Village, Kuala District, Langkat Regency in 2021 as many as 12 people (60%). The effect on breast milk production of pregnant women who experienced an increase after being given katuk leaf vegetables was 14 people (70%). It is recommended to health workers, especially midwives, to provide counseling to pregnant women about the benefits of katuk leaf vegetables on breast milk production.